Clinical analysis of gynecological diseases in postmenopausal women in tertiary care centre - Parihar, Bharti Choudhary; Tiwari, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
ABSTRACT Background: Menopause is a natural step in ageing process represents the period end of menstruation after last menstrual period in previous 12 months. Gynaecological disorder in older women differs from those who are younger. Disorders peculiar to ageing are pelvic organ prolapse, urinary incontinence, genital infections and malignancies. Present study is contemplated with a view to assess the magnitude of postmenopausal gynaecological morbidity. The goal of this study was to assess the age of onset of menopause and the spectrum of different gynaecological diseases, their incidence, diagnosis and treatment modality in postmenopausal females. Methods: A Prospective observational study of postmenopausal females attending Gynecology OPD or admitted in Sultania Zanana Hospital, Bhopal was carried out between July 2014 to June 2015. Total 401 postmenopausal females were included. Age of menopause and detail of all gynecological problems were recorded using predesigned proforma. Results: The study population was drawn from both rural (41.4%) and urban (58.8%) areas. Mean age of onset of menopause was 48.01 years in study population. In all, 28.4% had pelvic organ prolapse, 26.6% had genital malignancies, 25.5% had urogenital infections and 17.7% had benign disorder like senile endometritis, fibroid uterus etc. Conclusions: Menopausal health has been one of the neglected area in our country and needs timely vital attention as they are at risk of developing various genital malignancies. This emphasises the need for a screening programme for Indian women in our scenario.